2015
DOI: 10.1007/s10457-015-9862-2
|View full text |Cite
|
Sign up to set email alerts
|

The restoration of termite diversity in different reforestated forests

Abstract: In this study we compare the richness, abundance and guild composition between two different reforestations in the meridional part of the Amazon. We test the hypothesis that the termite community is affected by the identity of the tree species used in reforestation. More precisely, we test whether the reforestation of a native species of fig (Ficus sp) is more efficient in restoring biodiversity than reforestation of exotic teak trees (Tectona grandis). We sampled the termite community in these reforested area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
(30 reference statements)
1
8
0
Order By: Relevance
“…(2010) for beetles and Paula et al. (2016) for termites. Among functional groups, predators and detritivores showed the patterns of abundance consistent with those described before, although detritivores only showed significant differences between young and mature forests (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…(2010) for beetles and Paula et al. (2016) for termites. Among functional groups, predators and detritivores showed the patterns of abundance consistent with those described before, although detritivores only showed significant differences between young and mature forests (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the effect of habitat fragmentation on the diversity of termite across forest landscape concluded that termite diversity decreases along the sequence from primary forest to secondary forest and food crop fields (Davies, 2002;de Souza & Brown, 1994). Other studies have shown that termite richness is higher in mature forest, intermediate in reforestation areas, and lower in secondary forest and pastures (de Paula, Silveira, Rocha, & Izzo, 2016). Since the rustic shade system of Boumnyebel and the moderate shade of Obala could be compared to secondary forest, and Kedia and Bakoa systems of very light shade and full sun cocoa to food crop fields, we can clearly see that the pattern of termite species richness observed in this study corroborates with previously reported results.…”
Section: Discussionmentioning
confidence: 99%
“…These sites were compared based on species abundance, species richness and functional diversity of termites as indicators of nutrient availability through decomposition. Reforestation sites were found to be similar to undisturbed native forest sites, showing that after 15 years the young planted forest developed a healthy nutrient cycling process (Paula et al 2015).…”
Section: Research Programsmentioning
confidence: 74%